P039 Integrating Maintenance Efficacy and Safety of Vedolizumab and Other Advanced Therapies for the Treatment of Ulcerative Colitis: A Network Meta-Analysis. (December 2019) - Jairath, Vipul; Chan, Keith; Lasch, Karen; Keeping, Sam; Agboton, Christian; Blake, Aimee; Jansen, Jeroen; Patel, Haridarshan
Abstract : BACKGROUND: Comparative efficacy and safety data for therapeutic options in ulcerative colitis (UC) are lacking. Intravenous (IV) vedolizumab (VDZ) was recently shown to be superior to subcutaneous (SC) adalimumab (ADA) in VARSITY, the first head-to-head randomized controlled trial (RCT) of biologic therapies in UC. The objective of this study is to provide estimates of the efficacy and safety of other biologic therapies and tofacitinib (TOFA) relative to VDZ IV, by means of a network meta-analysis (NMA). METHODS: Relevant RCTs of VDZ (IV and SC), ADA, infliximab (IFX), golimumab (GOL), ustekinumab (UST), and tofacitinib (TOFA) were identified through a targeted literature review. Efficacy outcomes in the maintenance period were remission and response at 52/54 weeks. Differences in study design (treat-through vs re-randomized) across the relevant RCTs were accounted for by assessing efficacy outcomes conditional on response at start of maintenance. For treat-through studies, this was response at 6/8 weeks. Safety outcomes were overall adverse events (AEs), serious AEs (SAEs), overall infections, serious infections, and AEs leading to discontinuation as reported at 52/54 weeks. Odds ratios (ORs) with 95% credible intervals (CrIs) were estimated using probit and binomial NMA models, with results presented with VDZ IV 300 mg Q8W as the reference group. Analyses were conducted for the overall study population, as well as separately for the anti-tumor necrosis factor (TNF)–naïve and –experienced populations. RESULTS: Sixteen RCTs evaluating 13 therapies were included in the NMAs. Connected networks could be created for all three populations in the maintenance (10 trials) period. In the overall population, relative to VDZ 300 mg Q8W, ADA 40 mg, GOL 50 mg, and UST 90 mg Q12W had significantly lower rates for maintenance of response (OR: 0.62 [95% CrI 0.45, 0.86], 0.54 [95% CrI 0.31, 0.94], 0.58 [95% CrI 0.34, 0.98], respectively) and maintenance of remission (OR: 0.62 [95% CrI 0.45, 0.86], 0.54 [95% CrI 0.30, 0.94], 0.58 [95% CrI 0.34, 0.98], respectively). All other treatments had similar maintenance of efficacy to VDZ 300 mg Q8W. For safety outcomes, GOL had significantly higher rates of overall AEs (GOL 100 mg OR: 2.17 [95% CrI 1.18, 4.00]; GOL 50 mg OR: 1.90 [95% CrI 1.02, 3.54]) relative to VDZ 300 mg Q8W. Both GOL 100 mg (OR: 1.84 [95% CrI 1.07, 3.18]) and TOFA 10 mg (OR: 2.03 [95% CrI 1.19, 3.55]) had significantly higher rates of infections, while UST 90 mg Q12W had significantly lower rates of infections (OR: 0.58 [95% CrI 0.33, 0.98]) relative to VDZ 300 mg Q8W. GOL 100 mg also had significantly higher rates of discontinuation due to AEs (OR: 3.43 [95% CrI 1.18, 10.22]). ADA 40 mg, IFX 10 mg/kg, and IFX 5 mg/kg were similar to VDZ 300 mg Q8W across all safety outcomes. CONCLUSION(S): Results from this NMA based on RCTs indicate a favorable benefit-risk profile for VDZ 300 mg Q8W compared with other advanced therapeutic options available for UC.